Examining the dependence of southward shift of westerly anomalies on El Niño intensity: implications for varied El Niño termination patterns - Jia, Yifan; Xie, Ruihuang (Frontiers in Earth Science, 2024)
The dependence of the southward shift of low-level westerly anomalies over the equatorial central Pacific on El Niño intensity during the mature winter was investigated through observational analyses and air–sea coupled model simulations. El Niño events are categorized into two types based on the presence or absence of such a southward westerly shift (SWS). El Niño events with an evident SWS (SWS El Niño) exhibit strong intensity in sea surface temperature anomalies, whereas those without a remarkable SWS (non-SWS El Niño) are weak. The strength of westerly anomalies of SWS El Niño is twice as large as those of non-SWS El Niño in mature winter and can induce larger growth of westerly anomalies south of the equator by two anomalous southward westerly advections. One is the advection of anomalous westerlies by climatological winter-mean northerlies, and the other is the advection of climatological zonal wind by anomalous westerlies. Observations and model simulations both indicate that the two types of El Niño terminate differently. The strong SWS El Niño decays initially in the equatorial central Pacific, induced by a large local discharge of mass and heat content associated with intense SWS and the subsequent westward sea current anomalies starting in the decaying spring. In contrast, the non-SWS El Niño terminates first in the far eastern Pacific by cool advection carried by local westward sea current anomalies in mature winter, which is then enhanced by poleward discharge associated with weak SWS in the equatorial central Pacific.